A COMPREHENSIVE EVALUATION MODEL FOR ISLAMIC VALUES EDUCATION IN SCHOOLS AND MADA’RIS - Abdulatip Amilin kanjang (Journal of Innovative and Creativity (Joecy), 2026)
Islamic Values Education plays a vital role in developing students' spiritual, moral, intellectual, and social character. However, many educational institutions continue to rely on conventional assessment approaches that primarily measure cognitive achievement while neglecting affective and behavioral dimensions of Islamic values. Despite the widespread implementation of Islamic Values Education, many institutions continue to face challenges in evaluating its effectiveness. Existing assessment approaches often focus on cognitive achievement while neglecting affective and behavioral outcomes. Consequently, there is a need for a comprehensive evaluation model that assesses the planning, implementation, outcomes, and sustainability of Islamic Values Education programs in schools and mada’ris. This study proposes a Comprehensive Evaluation Model for Islamic Values Education applicable to both formal schools and traditional and modern mada’ris. The model integrates curriculum evaluation, instructional practices, student character development, institutional culture, community involvement, and long-term behavioral outcomes. Employing a qualitative library research design, the study synthesizes contemporary educational evaluation theories and Islamic educational principles derived from the Qur’an, Sunnah, and classical Islamic scholarship. The findings reveal that effective Islamic values education requires multidimensional evaluation encompassing knowledge acquisition, value internalization, behavioral manifestation, and social impact. The proposed model offers a systematic framework for educators, administrators, policymakers, and researchers to assess and improve the implementation of Islamic values education across diverse educational settings.